35. THE THERAPEUTIC EFFECT OF THE NGUYEN VAN HUONG HEALTH-PRESERVING EXERCISE ON INSOMNIA IN PATIENTS WITH CERVICOBRACHIAL SYNDROME (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the effect of Nguyen Van Huong health-preversing exercise on isomnia in patients with cervicobrachial syndrome.Subjects: A total of 50 inpatients aged 38 to 80 years diagnosed with insomnia and cervicobrachial syndrome at Department of Traditional Medicine, Saint Paul General Hospital, from October 2024 to July 2025.Methods: A clinical interventional study with a pre- and post-treatment comparison. Patients were received treatment for cervicobrachial syndrome using electro-acupuncture and acupressure massage following the Ministry of Health’s protocol, combined with Nguyen Van Huong health-preserving exercise during a 15-day period.Results: After treatment, the average sleep duration increased from 3.54 ± 0.84 (hours) to 5.26 ± 0.85 (hours); sleep onset latency decreased from 80.80 ± 31.93 (minutes) to 42.60 ± 25.50 (minutes); PSQI score decreased from 17.22 ± 1.88 to 12.26 ± 2.13 (points); VAS decreased from 5.80 ± 0.40 to 3.30 ± 0.51 (points). All changes were statistically significant (p < 0.05).Conclusion: The Nguyen Van Huong health-preserving exercise method helps improve sleep duration, sleep onset latency, and reduce PSQI scores in patients with cervicobrachial syndrome.
Keywords: Insomnia, cervicobrachial syndrome, Nguyen Van Huong health-preserving exercise.